A predator–prey based mathematical model of the bone remodelling cycle: Exploring the relationship between the model parameters and biochemical factors. (October 2014) - Ji, Bing; Yang, Qing; Genever, Paul G; Patton, Ronald J; Fagan, Michael J
Bone remodelling is a vital process which enables bone to repair, renew and optimize itself. Disorders in the bone remodelling process are inevitably manifested in bone-related diseases, such as hypothyroidism, primary hyperparathyroidism and osteoporosis. In our previous work, a predator–prey based mathematical model was developed to simulate bone remodelling cycles under normal and two pathological conditions, hypothyroidism and primary hyperparathyroidism, for trabecular bone at a fixed point. However, the biochemical meanings of the model parameters were not fully explored. This article first extends the previous work by proposing relationships between the model parameters and biochemical factors involved in the bone remodelling process and by examining whether those relationships do predict the behaviours observed in vivo. The model is then applied to the simulation and investigation of bone remodelling of postmenopausal osteoporosis. The proposed connections are supported by good agreement between the model simulations and published experimental observations for the normal condition and all three pathological variations in bone remodelling.